Portrait of rural emergency departments in Québec and utilization of the provincial emergency department management Guide: cross sectional survey - Fleet, Richard (BMC Health Serv Res, 2015)
BACKGROUND: Rural emergency departments (EDs) constitute crucial safety nets for the 20 % of Canadians who live in rural areas. Pilot data suggests that the province of Québec appears to provide more comprehensive access to services than do other provinces. A difference that may be attributable to provincial policy/guidelines “the provincial ED management Guide”. The aim of this study was to provide a detailed description of rural EDs in Québec and utilization of the provincial ED management Guide. METHODS: We selected EDs offering 24/7 medical coverage, with hospitalization beds, located in rural or small towns. We collected data via telephone, paper, and online surveys with rural ED/hospital staff. Data were also collected from Québec’s Ministry of Health databases and from Statistics Canada. We computed descriptive statistics, ANOVA and t-tests were used to examine the relationship between ED census, services and inter-facility transfer requirements. RESULTS: A total of 23 of Québec’s 26 rural EDs (88 %) consented to participate in the study. The mean annual ED visits was 18 813 (Standard Deviation = 6 151). Thirty one percent of ED physicians were recent graduates with fewer than 5 years of experience. Only 6 % had residency training or certification in emergency medicine. Teams have good local access (24/7) to diagnostic equipment such as CT scanner (74 %), intensive unit care (78 %) and general surgical services (78 %), but limited access to other consultants. Sixty one percent of participants have reported good knowledge of the provincial ED management Guide, but only 23 % of them have used the guidelines. Furthermore, more than 40 % of EDs were more than 300 km from levels 1 to 2 trauma centers, and only 30 % had air transport access. CONCLUSIONS: Rural EDs in Québec are staffed by relatively new graduates working as solo physicians in well-resourced and moderately busy (by rural standards) EDs. The provincial ED management Guide may have contributed to this model of service attribution. However, the majority of rural ED staff report limited knowledge or use of the provincial ED management Guide and increased efforts at disseminating this Guide are warranted.